2012
DOI: 10.1103/physrevc.86.067305
|View full text |Cite
|
Sign up to set email alerts
|

High-spin rotational bands in123I

Abstract: High-spin states in 123 I were populated in the reaction 80 Se( 48 Ca,p4n) 123 I at a beam energy of 207 MeV and γ -ray coincidence events were measured using the Gammasphere spectrometer. Three weakly populated, high-spin rotational bands have been discovered with characteristics similar to those of the long collective bands recently observed in other nuclei of this mass region. Configuration assignments are proposed based on calculations within the framework of the cranked Nilsson-Strutinsky approach.The nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The seven unconnected high-spin bands exhibit features similar to those of the long collective bands discovered recently in several nuclei of the region with neutron numbers between N = 68 and 72 [10,12,[15][16][17][18]. Configurations for the new high-spin structures are suggested on the basis of comparisons with the results of CNS calculations.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…The seven unconnected high-spin bands exhibit features similar to those of the long collective bands discovered recently in several nuclei of the region with neutron numbers between N = 68 and 72 [10,12,[15][16][17][18]. Configurations for the new high-spin structures are suggested on the basis of comparisons with the results of CNS calculations.…”
Section: Discussionsupporting
confidence: 64%
“…In several recent studies, high-spin rotational bands with large deformation were observed in nuclei with neutron number N = 68-72; i.e., in 120 Te [10], 123 I [12], 125 I [16], 125 Xe, [17], 126 Xe [18], and 124 Ba [15]. Some of these sequences extend into the spin-60 region.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations